2015
DOI: 10.1016/j.pharep.2014.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitric oxide synthase or cyclooxygenase inhibitors on cannabinoids activity in streptozotocin-induced neuropathy

Abstract: The results of this study seemed to indicate that the interaction between cannabinoid, COX-2 and NOS(s) systems might exist. Concomitant administration of small doses of CB1 and/or CB2 receptor agonists and COX-2 or NOS inhibitors can be effective in the alleviation of diabetic neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…According to the authors, the use of a specific nNOS inhibitor (7-Ni) and a relatively selective inhibitor of iNOS (L-NIL) showed a positive impact over the analgesic effect of two cannabinoid receptors agonists. Such finding suggests that CBD might not only modulate the expression and activity of NOS isoforms, but also have an inhibitory effect on the analgesia and anti-inflammatory pathways activated by cannabinoids agonists ( 36 ). In this study, we observed the reduction of nitrite/nitrate concentration in the GCBD group in comparison to the G group; values were similar to the groups C and CBD, which indirectly shows the reduction of NO concentration in the treated group in comparison to the diseased non-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, the use of a specific nNOS inhibitor (7-Ni) and a relatively selective inhibitor of iNOS (L-NIL) showed a positive impact over the analgesic effect of two cannabinoid receptors agonists. Such finding suggests that CBD might not only modulate the expression and activity of NOS isoforms, but also have an inhibitory effect on the analgesia and anti-inflammatory pathways activated by cannabinoids agonists ( 36 ). In this study, we observed the reduction of nitrite/nitrate concentration in the GCBD group in comparison to the G group; values were similar to the groups C and CBD, which indirectly shows the reduction of NO concentration in the treated group in comparison to the diseased non-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Several DN treatments targeting COX-2 have been reported, including rutin in combination with nimesulide (55), Juglans regia L. leaf extract (56) and curcumin (57). As a known inhibitor of COX-2, CXB has been demonstrated to reduce neuropathic pain caused by DN in rats (27,58). However, to the best of our knowledge, the present study is the first to reveal a possible mechanism for CXB in the treatment of DN.…”
Section: Discussionmentioning
confidence: 74%
“…( 45 ) have shown that COX-2 can lead to destruction of pancreatic tissues in diabetes, suggesting that regulating COX-2 pathway is a potential therapeutic strategy to control diabetic peripheral neuropathy. Several studies have shown that COX-2 and iNOS inhibitors can effectively alleviate diabetic neuropathic pain in STZ-induced neuropathy ( 46 ). COX-2 and iNOS also contribute to STZ-induced diabetic hyperalgesia.…”
Section: Resultsmentioning
confidence: 99%